The Effect Of Coaching And Supervision On Employee Performance At The Population And Civil Registration Office (DUKCAPIL) Of Lahat Regency - Geby Utami; Marko Ilpiyanto; Titi Hasanah (Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to determine the effect of guidance and supervision on employee performance at the Population and Civil Registration Office (DUKCAPIL) of Lahat Regency. The variables in this study are guidance (X1), supervision (X2), and performance (Y). The data analysis methods used are Instrument Testing (Reliability Test, Validity Test), Classical Assumption Testing (Normality Test, Heteroscedasticity Test, Multicollinearity Test), Multiple Linear Regression Analysis, Hypothesis Testing (T Test and F Test), and Determination Coefficient Test. The results of the study show that (1) Coaching has a significant partial effect on Employee Performance, as can be seen from the t-value > t-table (6.208 > 2.010). (2) Supervision has a significant partial effect on Employee Performance, as seen from the t-value > t-table (2.944 > 2.010). (3) Coaching and supervision have a significant simultaneous effect on Employee Performance, as seen from the calculated f value > table f value (79.933 > 4.038) and the significance value is smaller than the significance level (a) 0.05 (0.000 < 0.05).